Comparative genotypic and pathogenic examination of Campylobacter concisus isolates from diarrheic and non-diarrheic humans - Inglis G Douglas; Kalischuk Lisa D (BMC Microbiology, 2011)
Abstract Background Campylobacter concisus is an emerging enteric pathogen, yet it is commonly isolated from feces and the oral cavities of healthy individuals. This genetically complex species is comprised of several distinct genomospecies which may vary in pathogenic potential. Results We compared pathogenic and genotypic properties of C. concisus fecal isolates from diarrheic and healthy humans residing in the same geographic region. Analysis of amplified fragment length polymorphism (AFLP) profiles delineated two main clusters. Isolates assigned to AFLP cluster 1 belonged to genomospecies A (based on genomospecies-specific differences in the 23S rRNA gene) and were predominantly isolated from healthy individuals. This cluster also contained a reference oral strain. Isolates assigned to this cluster induced greater expression of epithelial IL-8 mRNA and more frequently contained genes coding for the zonnula occludins toxin and the S-layer RTX. Furthermore, isolates from healthy individuals induced greater apoptotic DNA fragmentation and increased metabolic activity than those from diarrheic individuals, and isolates assigned to genomospecies A (of which the majority were from healthy individuals) exhibited higher haemolytic activity compared to genomospecies B isolates. In contrast, AFLP cluster 2 was predominated by isolates belonging to genomospecies B and those from diarrheic individuals. Isolates from this cluster displayed greater mean epithelial invasion and translocation than cluster 1 isolates. Conclusion Two main genetically distinct clusters (i.e., genomospecies) were identified among C. concisus fecal isolates from healthy and diarrheic individuals. Strains within these clusters differed with respect to clinical presentation and pathogenic properties, supporting the hypothesis that pathogenic potential varies between genomospecies. ALFP cluster 2 isolates were predominantly from diarrheic patients, and exhibited higher levels of epithelial invasion and translocation, consistent with known roles for these factors in diarrhoeal disease. Conversely, isolates from healthy humans and AFLP cluster 1 or genomospecies A (which were predominantly isolated from healthy humans) exhibited increased haemolytic ability, apoptotic DNA fragmentation, IL-8 induction, and/or carriage of toxin genes. Given that this cluster contains an oral reference strain, it is possible that some of the AFLP cluster 1 isolates are periodontal pathogens and may cause disease, albeit via a different mechanism than those from AFLP cluster 2.